Did Magnet Schools Improve Student Educational Outcomes as a Tool of Desegregation? - (:unkn) unknown (My University, 2016)
Magnet schools were implemented in American school districts beginning in the 1970s as part of desegregation plans often required by court order. Magnet schools had three primary goals: provide innovative educational programming, attract students from across school districts, and assist with desegregation. Research evaluating the implementation of magnet schools found that they did effectively desegregate schools (Arcia 2006; Steel and Levine 1994). However, the educational outcomes of magnet schools have not been evaluated, particularly using longitudinal student data, to evaluate magnet school effectiveness. Popular press, the use of effective pedagogy, selection procedures, and exclusivity lead to expectations that magnet schools provide better educational outcomes. On the contrary, isomorphism in school management and the implementation of teaching practices lead to the expectations that magnet schools have similar outcomes to other public high schools. This study investigates the effect of attending a magnet high school in the tenth grade to find whether attendance impacted educational expectations or test scores in twelfth grade, prompt matriculation to postsecondary education, and educational attainment by age 26. Using propensity score weighting, magnet students are compared to comprehensive high school students. Magnet schools did not show an impact on the educational outcomes studied except for several findings among Asian students who experienced higher test scores and educational expectations than their non-magnet counterparts.
Keywords: Desegregation; Education; Longitudinal; Magnet Schools; Propensity Score; School Choice